(untitled) (Semiárida, 2020)
The effects of the dwarfing genes Rht1, Rht2 and Rht3, alone or in combination, on wheat , plant height, number of tillers, kernerl (grain) weight, yield, spike length, number of kernels per spike, number of spiklets per spike, number of kernels per spiklets, time to heading, width and length of flag leaf and foliar area, were studied. Isogenic Iines, with and without dwarfing genes, developed from the cultivars Maringá and Nainari 60 were used. The dwarfing genes decreased plant height,kernerl weight and flag leaf length and increased the number of kernels per spiklets, number of kernels per spike, flag leaf width and time lo heading. The combination of Rht1 + Rht2 and the allele Rht3, accentualed these effects (p<0.05). The Rht alleles did not have significant effects on the other characlers studied.